Healing the Past by Nurturing the Future: Aboriginal parents' views of what helps support recovery from complex trauma: Indigenous health and well-being: targeted primary health care across the life course. (30th September 2021) - Chamberlain, Catherine; Clark, Yvonne; Hokke, Stacey; Hampton, Angela; Atkinson, Caroline; Andrews, Shawana
Abstract: We aimed to understand support needs for Aboriginal and Torres Strait Islander parents experiencing complex trauma.Becoming a parent is an exciting yet challenging transition, particularly for parents who have experienced past hurt in their own childhood which can have long lasting effects, including complex trauma. Complex trauma-related distress can make it harder to care for a baby, but the parenting transition offers unique opportunities for recovery. This formative research is part of a community-based participatory action research project which aims to co-design perinatal awareness, recognition, assessment and support strategies for Aboriginal and Torres Strait Islander parents experiencing complex trauma. We used an Indigenist approach and grounded theory methods. Aboriginal and Torres Strait Islander parents who were pregnant and/or have children up to two years old were recruited through perinatal care services and community networks in three Australian sites (Alice Springs, Adelaide and Melbourne). Parents were offered a group discussion or individual interview, facilitated by Aboriginal researchers. Third-person scenarios and visual tools were used to facilitate reflections about the impact of past experiences, what keeps parents strong, hopes and dreams, and what is needed to achieve those dreams. Parents were also shown themes from a previous systematic review of parents' experiences as a prompt to identify any additional key issues. Seventeen Aboriginal and Torres Strait Islander parents participated in August to September 2019. Most were mothers (n = 15).  The study's grounded theory methods provided the foundation of a theoretical supposition that positions the transformation of the compounding cycle of trauma, to a reinforcing cycle of nurturing at the intersection of: 1) parents' connectedness; 2) social and emotional wellbeing; and 3) the transition to parenting. Unique opportunities and challenges situated at the interface are bound to the compounding or reinforcing nature of the intersecting factors. Findings reveal complexity, differing experiences by gender and age, as well as within and between communities.